(untitled) (Contemporary Issues in Social Sciences and Management Practices, 2024)
Iran’s nuclear program has been a constant priority agenda of international non-proliferation community for decade’s now. The Comprehensive Framework for Joint Plan of Action (JCOP) concluded as a result of intensive negotiations among negotiating parties on April 2, 2015. This deal was considered as a diplomatic breakthrough with regard to Iran’s nuclear program. President Trump withdrew from the deal unilaterally in 2018 on the pretext of being ineffective in curtailing Iran’s missile program and offensive proliferation designs. Iran also declared not to comply the provisions of deal as retaliation of US unexpected exit. After President Biden’s ascending to power prospects of renegotiations brightened. However, despite few attempts, no tangible step of concrete negotiations has taken so far. This paper endeavors to narrate the course of Iran’s nuclear deal with exclusive focus on post US withdrawal events. The paper endeavored to analyze responses of different US administrations towards the deal. For instance, nuclear deal concluded and came into force under Obama’s administration; US unilaterally withdrew from the deal under Trump administration, and Biden’s administration struggling to renegotiate the deal. A holistic review of the deal including major events, would help to understand US threat perceptions vis-à-vis a nuclear Iran and the handling of this threat perception under different administrations, reveling the fault-lines between democrats and republicans on Iranian nuclear deal issue at one hand and US and other negotiating partners at other hand. However, despite the divergent opinions to handle nuclear Iran, all parties seem to converge on one point, to avoid military confrontation in Middle East.